Selected Aspects of Medical Equipments and Instruments Industries in the Philippines - Oscar F. Picazo (Philippine Institute for Development Studies (PIDS), 1995)
The objectives of this study are to construct a profile of the medical instruments and equipment sector and to identify policy issues related to the acquisition, diffusion and use of pharmaceuticals and nonmedical supplies. The discussions in this paper are geared towards the synthesis of overall policy questions rather than analysis and testing of a particular hypothesis.
Keywords: 330; Young's theorem